Clinical diagnosis of hyposalivation in hospitalized patients - Berti-Couto, Soraya de Azambuja (2012)
OBJECTIVE: The aim of this study was to evaluate the effectiveness of clinical criteria for the diagnosis of hyposalivation in hospitalized patients. MATERIAL AND METHODS: A clinical study was carried out on 145 subjects (48 males; 97 females; aged 20 to 90 years). Each subject was clinically examined, in the morning and in the afternoon, along 1 day. A focused anamnesis allowed identifying symptoms of hyposalivation, like xerostomia complaints (considered as a reference symptom), chewing difficulty, dysphagia and increased frequency of liquid intake. Afterwards, dryness of the mucosa of the cheecks and floor of the mouth, as well as salivary secretion during parotid gland stimulation were assessed during oral examination. RESULTS: Results obtained with Chi-square tests showed that 71 patients (48.9%) presented xerostomia complaints, with a significant correlation with all hyposalivation symptoms (p